Development of media package for creating awareness among rural women regarding use of Aloe vera - Mahal, Parneet; Kanwaljit Kaur,; Mandeep Sharma, (Indian Journal of Extension Education, 2025)
To check the effectiveness of developed media package on Aloe vera, a sample of 130 rural women from 13 villages of Ludhiana district was purposively selected. The data were collected in April and May 2024 from Ludhiana district and were analyzed with the help of percentage, mean score and paired t-test.The media package containing printed material, whatsapp messages and video clips on Aloe vera was developed and validated by 30 Subject Matter Specialists. Effectiveness of media package was measured in terms of mean change in health benefit, its nutritive value and usage into different forms for curing various ailments and awareness level of the respondents after the exposure of the media package. Interview schedule was constructed to collect data into two phases. Before exposure to media package data regarding status of growing and awareness level of Aloe vera plant. Printed materials related to plant were distributed to the respondents. WhatsApp message and video clips were sent to the rural women. After 25 days post awareness data were collected. Results of the study showed significant change between pre and post awareness mean score for its all parameters. So, the prepared media package was proved to be effective to motivate people.